Learning methodologies in distance education: Diversity and challenges - Rocha, Jorge Vieira da (2022)
With technological advances, digital tools have become present in all segments of work and the same has happened with education. New technologies associated with distance education (EAD) projects increase the ability to access a professional training program. As a result, new teaching methodologies are used by teachers in order to bring better quality knowledge to their students. The democratization of teaching and the growth of new technology, methodologies and distance learning processes become more applicable and flexible to those who want to study. The objective of the study is to know how learning methodologies contribute to this evolution. The methodology carried out is based on exploratory research from which a survey of Thesis, dissertation and scientific articles that bring to the discussion the causes of dropouts and dropout in EAD, between the years 2002 and 2022.